2002
DOI: 10.1046/j.1439-0450.2002.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Antimicrobial Susceptibility of Coagulase Positive Staphylococci Isolated from Healthy Dogs and Dogs Suffering from Otitis Externa

Abstract: A total of 67 strains of coagulase positive staphylococci isolated from healthy dogs and dogs suffering from otitis externa were studied. Twenty-two isolates were from healthy dogs (five from hound dogs and 17 from companion dogs) and 45 from dogs suffering otitis externa (14 from hound dogs and 31 from companion dogs). Presumptive identification was attempted using the following tests: production of acetoin, anaerobic utilization of mannitol, acid production from mannitol, presence of beta-galactosidase, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
1
5
0
3
Order By: Relevance
“…Staphylococcus intermedius represented a major proportion of the canine and feline isolates identified in the Bft-GermVet study and the results were comparable with those of recent studies on S. intermedius isolated from dogs suffering from pyoderma or otitis externa [24][25][26][27]. One of these studies also investigated the genetic background of the observed macrolide-lincosamide-streptogramin B (MLS B ) resistance [27].…”
Section: Discussionsupporting
confidence: 81%
“…Staphylococcus intermedius represented a major proportion of the canine and feline isolates identified in the Bft-GermVet study and the results were comparable with those of recent studies on S. intermedius isolated from dogs suffering from pyoderma or otitis externa [24][25][26][27]. One of these studies also investigated the genetic background of the observed macrolide-lincosamide-streptogramin B (MLS B ) resistance [27].…”
Section: Discussionsupporting
confidence: 81%
“…The external auditory meatus of dogs is inhabited by various micro-organisms. Among them, different Staphylococcus species play a significant role (Junco and Barrasa, 2002). The most important pathogens are coagulase-positive staphylococci (CPS), especially S. intermedius (Hajek, 1976) and, to a lesser extent, S. aureus (Kloos and Schleifer, 1986) or S. schleiferi ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Os primeiros relatos com uso de tobramicina in vitro citavam 100% de eficiência do antimicrobiano contra cepas de Staphylococcus sp. Houve uma redução progressiva desse percentual (Junco & Barrasa, 2002) e em 2003 encontrava-se em torno de 82% . Acredita-se que esse percentual tenha reduzido significativamente, pois dados encontrados neste trabalho apresentaram 0 e 30% de eficiência para este antimicrobiano em relação às bactérias S. epidermidis e S. Pseudintermedius, respectivamente.…”
Section: Discussionunclassified
“…(Bornand, 1992, Leite, 2003, Silva, 2001, Junco & Barrasa, 2002. Tais resultados diferem dos apresentados no presente trabalho, onde a norfloxacina apresentou uma eficiência mediana (60 e 33%) para S. pseudintermedius e S. epidermidis.…”
Section: Discussionunclassified
See 1 more Smart Citation